Comparison of two extenders for cryopreservation of native chicken (Gallus gallus domesticus) sperm in the Philippines. - Guieb, Heinz Kesniel D. (2014)
This paper presents the optimum extender for the cryopreservation of native chicken sperm. Two chicken extenders were compared in this study: Lake?s Extender and Extender AU. Semen were collected from six male chickens and mixed with the extenders in a 1:1 ratio and observed for 0 h, 6 h, 12 h, 24 h, 36 h, 48 h, and 72 h. Sperm concentration, morphology, and motility were determined. Results showed that Extender AU was able to produce viable sperms having a sperm motility of >30% after 24 h of storage at 5oC. On the other hand, the Lake?s Extender was not able to produce viable sperm after 6 h of storage at 5oC. However, both extenders were able to produce an acceptable range of normal sperm morphology (>70%). The work presented here can be used for future studies for the storage of the native chicken sperm in the Philippines.
Thesis (BS Biology). University of the Philippines Cebu